Evaluation of certain biochemical parameters of wrestlers before and after the 20 m shuttle run test - Türkmen , M. (Journal of Education and Training Studies, 2017)
This study was conducted to determine the acute changes after the 20 m shuttle run test in the biochemical parameters and heart rates of wrestlers competing in international competitions on a study population of 21 wrestlers. The mean age of participants was 24.14±2.01years, mean heights 176±0.06 cm, body weight 76.48±14.76 kg, MaxVO2 52.78±3.20 ml/kg/min, and mean BMI 24.44±2.63 kg/m2.